145k views
4 votes
Please simplify this equation

Please simplify this equation-example-1
User Oedum
by
5.1k points

2 Answers

4 votes

Answer:


\frac{ {9}^(2) }{ {9}^(7) } \\ = {9}^( - 5 ) = \frac{1}{ {9}^(5) }

yes, the last answer is correct....

User Spiff
by
6.3k points
1 vote

Answer:

1/9^5

Explanation:

9^2 / 9^7

We know that a^b / a^c = a^(b-c)

9^2 / 9^7 = 9^(2-7) = 9^-5

But we don't like negatives in the exponents

We know that a^-b = 1/ a^b

9^-5 = 1/9^5

User Pronix
by
5.9k points